2012
DOI: 10.4236/njgc.2012.23017
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Characterization of Mullite Refractory Products from Moroccan Andalusite

Abstract: Enrichment of schist mined in Morocco resulted in an extract essentially made of andalusite, quartz and muscovite, which was investigated with the aim to synthesize mullite refractory materials. X-ray diffraction analysis was used to assess phase transformations upon heating at different temperatures. Mullite formation starts as early as 1200℃ and seems almost total at 1450℃. This process correlates with a weak shrinkage (3.5% at 1450℃) and the formation of an important glass phase. Green compacts obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…It is known that mullite is a promising candidate for advanced ceramic applications due to its high melting point (1840 1C), low-thermal expansion (5 Â 10 À 6 K À 1 in the temperature range 20-800 1C), good thermal shock resistance, high creep resistance (dε/dt4 10 À 10 s À 1 at 1200 1C), flexural strength (above 360 MPa) [34], chemical stability [35] and high refractoriness [36].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that mullite is a promising candidate for advanced ceramic applications due to its high melting point (1840 1C), low-thermal expansion (5 Â 10 À 6 K À 1 in the temperature range 20-800 1C), good thermal shock resistance, high creep resistance (dε/dt4 10 À 10 s À 1 at 1200 1C), flexural strength (above 360 MPa) [34], chemical stability [35] and high refractoriness [36].…”
Section: Introductionmentioning
confidence: 99%
“…The low density of the A10‐1650‐1 h and A10‐1650‐3 h samples may relate to the high amount of SiO 2 phase caused by a greater amount of andalusite. The heavy fall in porosity was the result of the glassy phase formation, which filled the open voids . This trend showed that, at the sintering temperature of 1650°C where the reaction sintering was carried out continuously by the addition of andalusite, the decomposition of zircon would be completed (constant porosity).…”
Section: Resultsmentioning
confidence: 96%
“…During the process, mullite precipitates and the excess silica creates a liquid phase, which is then reacted again with the alumina matrix and produces the mullite phase . The liquid phase, which is formed by reactions between the free silica, alumina, and alkaline, in accordance with the ternary SiO 2 ‐Al 2 O 3 ‐R 2 O system, is responsible for densification of the compacts and improvement of the sintering state . The formation of the liquid phase leads to the accerelation of mullitization and also reacts with alumina to form secondary mullite.…”
Section: Resultsmentioning
confidence: 99%
“…It confirms that mullite does not contain any foreign inclusions. 29 The tested sample shows the Al/Si ratio to be ≈ 0.84 as shown in Table 2. It is less than the stoichiometric composition of mullite (Al/Si 3:1).…”
Section: Morphological Analysis and Spectral Changes Before And After Mb Adsorptionmentioning
confidence: 94%